Revitalizing Traditional Game as Learning Media: Harnessing KOBI (Kartu Operasi Bilangan Integrasi) to Foster Creative Thinking Learning - Mukti, Taufiq Satria; Rifqy, Muhammad Iqbal; Ilmi, Ilham Imtiyazil; Arianti, Putri Dwi; Fitri, Kartika Satya Novia (Proceeding of International Conference on Islamic Education (ICIED); Vol 9 No 1 (2024): Proceeding of International Conference on Islamic Education (ICIED)DO - 10.18860/icied.v9i1.3141, 2024)
Students must develop their creative thinking abilities in order to tackle challenging issues with original answers. However, a lot of students find it difficult to evaluate data and choose practical approaches to solving problems, which frequently leads to a lack of inventiveness. This study presents Kartu Operasi Bilangan Integrasi (KOBI), a learning tool based on cards that uses educational games to foster students' creative thinking. This quantitative study, which employed a pre-test and post-test experimental design, was carried out with seventh-grade students at MTsN Kota Batu to assess improvements in their capacity for creative thought. Tests and questionnaires were used to gather data, and SPSS was used for both descriptive and inferential statistical analysis. With an average improvement of 52.34 points, the results showed that KOBI media greatly improved students' creative thinking.